2015
DOI: 10.1002/hed.24230
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in cN0 squamous cell carcinoma of the lip: A retrospective study

Abstract: SLNB can be a viable staging technique in SCC of the lip. Tumor diameter of ≥ 20 mm and increasing tumor thickness seem to delineate higher risk for regional disease in our study. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1375-E1380, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…Despite the disarray, studies have shown that predictive value of regional node metastasis is greater with SLNB than conventional staging procedures (physical exam and imaging) in regards to cutaneous SCC . It has been demonstrated to be an important tool in staging clinically node negative SCC cases, as up to 11.5% of cases in a particular study were upstaged due to biopsy results alone . The positivity rate of SLNB in clinically node negative patients amongst various studies was found to be 14.6%.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the disarray, studies have shown that predictive value of regional node metastasis is greater with SLNB than conventional staging procedures (physical exam and imaging) in regards to cutaneous SCC . It has been demonstrated to be an important tool in staging clinically node negative SCC cases, as up to 11.5% of cases in a particular study were upstaged due to biopsy results alone . The positivity rate of SLNB in clinically node negative patients amongst various studies was found to be 14.6%.…”
Section: Discussionmentioning
confidence: 93%
“…Birçok çalışmada tümörün boyutu, evresi, derinliği, farklılaşma derecesi ve perinöral invazyon varlığı gibi faktörler ile boyun metastazı arasındaki ilişki incelenmiştir. [8,9] Dudak kanserlerinin lenf nodu metastaz oranları %3-29 arasın-da değişmekle beraber boyun metastazlarının tümörün boyutuyla ilişkili olduğu ve T 1 tümörlerde metastaz oranının %0-15, T 2 tümörlerde %11-35 ve T 3 tümörlerde %63 olduğu bildirilmiştir. [21,22] Bizim çalışmamızda da literatürle uyumlu olarak T 1 tümörlerde %5, T 2 tümörler-de %36.4 ve T 3 tümörlerde %50 metastaz oranları tespit edildi.…”
Section: Discussionunclassified
“…Çalışmamızda tümörün boyutu ile boyun metastazı arasındaki ilişki incelendiğinde, literatürle uyumlu olarak 20 mm'den büyük tümörlerde boyun metastazı riski istatistiksel olarak anlamlı oranda artmaktaydı. [8,9] Tümörün derinliği ile boyun metastazı arasındaki iliş-kinin incelendiği çalışmaların bir kısmında sınır değer 5 mm, bir kısmında ise 6 mm olarak kabul edilmiş ve tümörün derinliği ile boyun metastazı arasında ilişki olduğu bildirilmiştir. [8,9] Bizim çalışmamızda ise sınır değer 6 mm olarak kabul edildi ve bu çalışmalarla benzer olarak tümör derinliğine bağlı olarak boyun metastazı riskinin arttığı bulundu.…”
Section: Discussionunclassified
See 2 more Smart Citations